Questioning the Role that Storytelling Can Play in Prefaring Children for Primary Education in Tanzania - Mhagama, Willy; Wang'uba Okello, Joel; Nsyengula, P., Stephen; Haule , J, Emmanuely (English Lecturers and Teachers Association (ELTA), 2025)
The central focus of this study was the importance of storytelling in preparing Tanzanian children for pre-primary education. Anchored in the socio-cultural practices propounded by Lev Vygotsky, the study was a collaborative effort that explores the significant yet under-researched role of oral storytelling in early childhood education, particularly in East Africa. Through observations, interviews, focus group discussions, and document analysis involving parents, teachers, and community members, the study investigates the impact of storytelling on various aspects of children's development, including communication skills, creativity, problem-solving abilities, confidence, language acquisition, teamwork, and moral values. The findings highlighted the multifaceted benefits of storytelling and propose evidence-based recommendations for stakeholders to promote and integrate storytelling into educational practices, making them an integral part of the research process. Keywords: Storytelling; Early Child Education; Sociocultural practices.